(3JSgjd GdeWdH aj JMUjd GdePgHs - (3YHO GdQMef Hf eMeO Hf CMeO Hf bOGeI GdebOSj GdLeGYjdj GdMfHdj, CHh GdaQL, TeS GdOjf , (B682 (3g`s; (3CHh YeQh GdOGfj , GHf GdUjQaj,J (B444 (3g` s ((3YHOGddg Hf YjSi Hf GHQGgje GdebOSj s)
(3ChdgG (B:s
(3cJGH GdYJb s
(3BNQgG (B:s
(3BNQ HGH GdGSJKfGA ai GdWdGb s
(3ef GdfSNI faSgGs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdMfHdjs